The Influence Of Plyometric And Lower Limb Power Training On Squat Jump In Participants Of Athletics Extracurricular At SMP Negeri 2 Abang - Desak Gede Suci Paramita; Wahjoedi Wahjoedi; Suratmin Suratmin (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze: (1) The differences in the influence of squat jump style on participants of athletics extracurricular who undergo alternate leg bound plyometric training and double leg bound plyometric training. (2) The interaction between plyometric training and lower limb power on squat jump style. (3) The differences in squat jump style results between alternate leg bound plyometric training and double leg bound plyometric training for participants with high lower limb power. (4) The differences in squat jump style results between alternate leg bound plyometric training and double leg bound plyometric training for participants with low lower limb power. The research method used is a quasi-experimental design with a 2x2 treatment by level factor design. The sample size used was 40 individuals determined from the categories of high lower limb power and low lower limb power. The instruments used were standing broad jump to measure lower limb power and squat jump. Data analysis technique used a two-way ANOVA with a significance level of 0.05. The results of this study show differences in the influence of squat jump style among extracurricular participants undergoing alternate leg bound plyometric training and double leg bound plyometric training. There is an interaction between plyometric training and lower limb power on squat jump style. Recommendations for extracurricular instructors include considering alternate leg bound plyometric training as an alternative method to improve squat jump style.